Pengaruh Peranan Bank Sampah Dalang Collection terhadap Kesejahteraan Karyawan Perspektif Ekonomi Syari’ah - Efendi, Rustam; Bakhri, Boy Syamsul; Mursi, Yuhermi Okta (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2018)
This research is based on the results of pre-research conducted by the writers after looking at “Dalang Collection”  Garbage Bank in Pekanbaru city which is an alternative solution in handling waste in Pekanbaru. Although it was only established in 2012, the “Dalang Collection”  Garbage Bank has been able to empower communities around to become more productive and earn income, especially for mothers. Therefore, the writers are interested in examining the influence of  roles of the “Dalang Collection”  Garbage Bank on employee welfare. The problem formulation of this study is how the “Dalang Collection”  Garbage Bank influences employee welfare and whether the role of the “Dalang Collection”  Garbage Bank on employee welfare is in accordance with the sharia  economic perspective. The research objective was to determine the influence of the role of the “Dalang Collection”  Garbage Bank on the welfare of employees and to know the extent of the influence of the role of the “Dalang Collection” Garbage Bank on employee welfare in accordance with the sharia economic perspective. In analyzing quantitative data, simple linear regression analysis is used where the calculation process uses SPSS for windows version 23.0. The sample of this study was 42 people. The results of this study note the role of “Dalang Collection” Garbage Bank on employee welfare has a very close relationship, this is known from the correlation coefficient of 90.1%. While the partial test results have a significant effect between the role of the ”Dalang Collection” Garbage Bank on employee welfare, it is known from the t-count (13.164) is greater than t-table (1.684). It means that partially it can be seen that the variable X (role) affects the variable Y (employee welfare). Employees of the “Dalang Collection” Garbage Bank have had moral welfare, spiritual welfare and social welfare while material welfare has not been fulfilled so that it cannot be said prosperous according to the sharia economic perception.